Overlay Spectrum Reuse in a Multicarrier Broadcast Network: Coverage Analysis - Alberto Rico-Alvariño; C. Mosquera; Fernando Pérez-González (The 13th IEEE International Workshop on Signal Processing Advances in Wireless Communications (SPAWC 2012), 2012)
A secondary cognitive user overlaying its message in a broadcast multicarrier network is studied. The secondary user exploits the primary message knowledge to convey its own information while preserving the primary user coverage area, determined by a bound on the BER, and taking into account the degradation due to the insertion of an echo in a dominant line of sight environment. The results are compared with those obtained when the coverage area is defined in capacity terms, and regardless of the degradation caused by the secondary replica of the primary message.
Keywords: cognitive radio; dynacs